2011
DOI: 10.1128/jcm.01131-10
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal RNA Sequence Analysis of Brucella Infection Misidentified as Ochrobactrum anthropi Infection

Abstract: A Brucella isolate was identified from purulent material collected during a hip surgery. Two previous blood cultures from the same patient yielded Ochrobactrum anthropi. After rRNA sequencing, all the isolates were identified as Brucella species and subsequently serotyped as Brucella suis. Misidentification of Brucella species remains a problem with bacterial identification systems. CASE REPORTA 62-year-old female presented to the emergency department with left hip pain and was unable to bear weight on that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
0
33
0
1
Order By: Relevance
“…Despite the publication of laboratory safety measures (15,16) and postexposure recommendations (17), laboratory exposures and laboratory-acquired brucellosis (LAB) cases continue to occur (18,19). In the United States, roughly 120 cases of brucellosis are reported annually.…”
mentioning
confidence: 99%
“…Despite the publication of laboratory safety measures (15,16) and postexposure recommendations (17), laboratory exposures and laboratory-acquired brucellosis (LAB) cases continue to occur (18,19). In the United States, roughly 120 cases of brucellosis are reported annually.…”
mentioning
confidence: 99%
“…e read with interest the paper "Ribosomal RNA Sequence Analysis of Brucella Infection Misidentified as Ochrobactrum anthropi Infection" by Horvat and colleagues (1). The paper reported that a Brucella isolate was misidentified as Ochrobactrum anthropi.…”
mentioning
confidence: 99%
“…Sequencing of the 16S rRNA gene, which is in widespread use for bacterial identification, can be misleading and Brucella organisms cannot be accurately distinguished from the closely related α-protobacterial Ochrobacterium species [72]. A novel recA gene-based, multi-primer, single-target PCR assay has been recently developed and succeeded in differentiating between brucellae and Ochrobacterium anthropi and O. intermedium [73], although the test has a more prolonged turnaround time and is more expensive than the FISH test.…”
Section: Identification Of Brucellae By Dna Technologymentioning
confidence: 99%